Geochemical Assessment of Heavy Metal Contamination in Coastal Sediment Cores from Usukan Beach, Kota Belud, Sabah, Malaysia. Issue 1 (1st August 2022) - Ling, S Y; Junaidi, A; Mohd Harun, A; Baba, M
Abstract: This article discussed on the status of heavy metals (As, Cr, Cu, Mn, Ni, Pb and Zn) pollution in coastal sediment cores and assess the sediment quality from Usukan Beach, Kota Belud. Several geochemical parameter analyses such as pH, moisture content (MC), organic matter (OM) and granulometric size were performed to identify the physico-chemical properties of sediments that affect the assessment of metal pollution. Heavy metals in the sediment samples were extracted using aqua regia methods and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) were employed for determination of heavy metals in extracted sediment solutions. The results show that the coastal sediment changes from acidic to alkaline when heading from inland to seaward direction, with an average pH of 5.6-8.5. The moisture content and organic matter fluctuate from low to moderately high, within the range of 4.9-21.9% and 0.30-6.73%, respectively. The coastal sediments are dominated by a sandy texture near the marine environment and change to sandy loam and sandy clay loam when heading toward the inland. The hierarchical average metal concentration shows Fe>Mn>Ni>Cr>Zn>Cu>Pb>As. Sediment quality assessment is evaluated based on the sediment quality guidelines (SQGs) and from the pollution indices such as geoaccumulation index (Igeo), enrichment factor (EF), contamination factor (CF), modified degree of contamination (mCd) and pollution load index (PLI). The results indicated the sediment has only low degree of contamination by anthropogenic sources and the current status of the study area is safe from pollution.